Soil Mesofauna Community Changes in Response to the Environmental Gradients of Urbanization in Guangzhou City - Yu, Shiqin; Qiu, Junliang; Chen, Xiaohua; Luo, Xiaofeng; Yang, Xiankun; Wang, Faming; Xu, Guoliang (Frontiers in Ecology and Evolution, 2021)
There has been a recent increase in interest on how urbanization affects soil fauna communities. However, previous studies primarily focused on some limited land use types or line transects of urban-rural gradients. At family and higher taxonomic levels, we investigated the changes of soil mesofauna communities (abundance, species richness, and community structure) with urbanization intensity along different disturbance features in 47 sites evenly located in downtown Guangzhou and adjacent regions. The 47 research sites were classified into four ecosystem types mainly according to the location (rural/urban), vegetation cover, and management intensity. In turn, the four types with increasing urbanization intensity were rural forest, urban forest, urban woodland, and urban park. Firstly, the role of urban soil property (soil physicochemical characteristic and soil heavy metal content) in regulating soil mesofauna community was investigated. The results showed that soil mesofauna abundance and diversity decreased with increasing soil pH, total nitrogen content (TN), and heavy metal comprehensive index (CPI). Soil Pb decreased soil mesofauna species richness (taxa number) and regulated soil mesofauna community structure. Secondly, we examined the effects of landscape changes on the soil mesofauna community. We found impervious surface (IS) ratio did not predict changes in soil mesofauna abundance, species richness, or community structure. Instead, IS ratio was positively correlated with soil pH, soil TN, and CPI. After excluding sites that belonged to rural forests and urban parks, site area was positively correlated with soil mesofauna abundance. Thirdly, our results revealed significant differences in soil property, landscape trait, and soil mesofauna community among the four ecosystem types. Interestingly, urban forest, the one lightly disturbed by urbanization, but not rural forest, had the highest soil mesofauna abundance. Soil mesofauna abundance in urban woodlands was similar to that in urban parks, which was about half of that in urban forests. Species richness in urban parks was 21% lower than that in rural forests. Our results also showed that urban woodland and urban parks had distinct mesofauna community structures compared to those in rural forests and urban forests. In conclusion, the present study suggested that (1) soil property changes due to urbanization, such as increased pH and heavy metal enrichment in urban soil, decreased soil mesofauna abundance and species richness, changed community structure, and mediated the effect of landscape change on soil mesofauna community; (2) however, soil and landscape changes could not explain the increase of abundance in urban forests, which supported the intermediate disturbance hypothesis.